MEMBANGUN KALIMAT TUNGGAL DAN KALIMAT MAJEMUK DALAM BAHASA BALI (KAJIAN DESKRIPTIF) - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Balinese language is one of the many regional languages that are still alive and well in thecountry of Indonesia which is well maintained by the speakers, namely ethnic Balinese. Balineseas a mother tongue or first language for the majority of Balinese has an important role, namelyas a symbol of pride, symbol of identity, and widely used as a communication tool in variousactivities in the household and outside the household which cover various activities of thecommunity's social life Bali. Based on a glimpse of the background above, it is necessary toexamine the following: (1) how to build a single Balinese sentence? and (2) How to build BalineseCompound Sentences? Related to the formulation of the problem to be discussed, the purpose ofwriting is: (1) to Know the Single Sentences of Balinese Language and (2) to Know the CompoundSentences of Balinese Language. Based on the above explanation, it can be concluded that theresults of this study are as follows: (1) Building a single sentence is an effort to develop asentence that relies on one pattern (clause), which consists of a subject and predicate (a sentenceconsisting of only one clause). Single sentences are the simplest sentences. (2) Building compoundsentences is an attempt to develop sentences, which are carried out by combining two or moresingle sentences, so that the new sentence contains two or more clauses.Keywords: Syntax, Single Sentences, Compound Sentences